GAYA HIDUP KONSUMEN WARUNG KOPI DI WILAYAH PERKOTAAN KABUPATEN JEMBER - Adi Prasodjo (UNEJ e-Proceeding)
The purpose of research is to know and understand consumer lifestyles coffee shop in the Urban Area of Jember. This descriptive study using an ethnographic approach. The research data consists of primary and secondary data. Primary data obtained from respondents and informants obtained through questionnaires and face to face interviews individually. Sampling was done by purposive sampling method, while data analysis using descriptive analysis. The results showed that the consumer lifestyle coffee shop consists of six categories, namely: the lifestyle of consumers in a buying atmosphere, consumers' lifestyles for socializing, lifestyle consumers to share and search for information, the lifestyle of consumers to the product, consumer lifestyle is becoming a habit and consumer lifestyle for recreation. The process of consumer purchases in the shop as much as 81.94% influenced by friends and almost 100% of consumers came to the coffee shop with her friend. Consumers feel satisfied with the purchase at a coffee shop at 97.22%.